Accurate quantitation of protein expression and site-specific phosphorylation - Oda, Y. (The National Academy of Sciences, 1999)
A mass spectrometry-based method is described for simultaneous identification and quantitation of individual proteins and for determining changes in the levels of modifications at specific sites on individual proteins. Accurate quantitation is achieved through the use of whole-cell stable isotope labeling. This approach was applied to the detection of abundance differences of proteins present in wild-type versus mutant cell populations and to the identification of in vivo phosphorylation sites in the PAK-related yeast Ste20 protein kinase that depend specifically on the G1 cyclin Cln2. The present method is general and affords a quantitative description of cellular differences at the level of protein expression and modification, thus providing information that is critical to the understanding of complex biological phenomena.